The crisis of Arab philosophical thought and its repercussions on reality - زملوط, رشا; إبراهيم, حامد (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The crisis of Arab philosophical thought today is due to a group of reasons that made its features appear within a picture characterized by ambiguity in its orientations. Topics that directly affect the reality and increase the effectiveness of the intellectual project. Therefore, this article aims to clarify some of the features of that crisis and its causes, and to show that Arab thought today must have a strong movement that transcends the setback it is going through and restores the intellectual compass to what it was according to a clear and well-defined approach.